PERBANDINGAN METODE PROBLEM SOLVING DAN METODE COURSE REVIEW HORAY TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X DI SMA NEGERI 8 GOWA - Linda, Erlina Linda; Karim, Syahruni; Taskirah, Taskirah (Guru Membangun, 2024)
This research is an experimental study which aims to determine the differences in Biology learning outcomes for Class X students at SMA Negeri 8 Gowa when using the Problem Solving learning method and the Course Review Horay method. The population in this study were all class X students of Gowa State High School, while the sample in this study was class The data analysis techniques used are descriptive analysis and inferential analysis.The results of this research indicate that the comparison of the Problem Solving learning method and the Course Review Horay method has a significant influence on student learning outcomes. The learning outcomes of students using the Problem Solving method have an average pre-test score of 62.63 and post-test of 77.11, showing significant improvement and meeting the complete learning criteria. Meanwhile, students who used the Course Review Horay method showed an average pre-test score of 63.63 and post-test of 88.48, showing better improvement and achieving minimum completeness. Thus, it can be concluded that the Course Review Horay method is more effective in improving student learning outcomes than the Problem Solving method in the context of this research